Role of Hippo Pathway-YAP/TAZ Signaling in Angiogenesis - Boopathy, Gandhi T. K.; Hong, Wanjin (Frontiers in Cell and Developmental Biology, 2019)
Angiogenesis is the highly coordinated process of formation of new blood vessels from pre-existing blood vessels. The process of development of the proper vascular network is a complex process that is crucial for the vertebrate development. Several studies have defined essential roles of Hippo pathway-YAP/TAZ in organ size control, tissue regeneration and self-renewal and identified this pathway as one of the central components in tissue homeostasis. There are mounting evidences on the eminence of Hippo pathway-YAP/TAZ in angiogenesis in multiple model organisms. Hippo pathway-YAP/TAZ is now demonstrated to regulate endothelial cell proliferation, migration and survival; subsequently regulating vascular sprouting, vascular barrier formation and vascular remodeling. Major intracellular signaling programs that regulate angiogenesis concomitantly activate YAP/TAZ to regulate key events in angiogenesis. In this review, we provide a brief overview of the recent findings in the Hippo pathway and YAP/TAZ signaling in angiogenesis and development.